Assessment of D-Dimers for the Early Prediction of Complications in Acute Pancreatitis. Issue 7 (August 2016) - Gomercic, Cécile; Gelsi, Eve; Van Gysel, Damien; Frin, Anne-Claire; Ouvrier, Delphine; Tonohouan, Marie; Antunes, Ophélie; Lombardi, Léa; De Galleani, Laurianne; Vanbiervliet, Geoffroy; Filippi, Jérôme; Schneider, Stéphane; et al.
Abstract : Objectives: Severe acute pancreatitis (AP) is characterized by early microcirculation defects causing hypercoagulability. The purpose of this study was to evaluate the early predictive value of D-dimers in complicated AP. Methods: This was a prospective single-center study conducted between September 2010 and April 2012. All patients had AP for less than 48 hours duration at admission. The plasma D-dimer level was determined at admission and every 12 hours over 3 days and compared to other validated severity criteria. Results: Of 71 patients admitted with AP, 36 (53.1%) developed complicated AP. A threshold D-dimer level greater than 1474 ng/mL at 48 hours after pain onset was predictive of complications with an area under the curve (AUC) of 0.76. Combining D-dimers and C-reactive protein levels at 48 hours increased the prediction of complications (AUC of 0.83). At 36 hours, D-dimers greater than 1474 ng/mL predicted the occurrence of complications with an AUC of 0.75. Conclusions: D-Dimer levels were predictive of complications of AP as early as 36 hours after the onset of pain. This simple and reproducible marker might be useful in clinical practice to improve the early management of complicated AP.